Learning through entertainment: The effects of Bollywood movies on the job-seeking behavior of South Asian female. (April 2016) - Rasul, Azmat; Raney, Arthur A
This study examined the relationship between exposure to Bollywood movies and job-seeking behavior of South Asian females. Using survey data collected from 132 female participants, we explored the effects of exposure to Bollywood movies on job search self-efficacy, enjoyment and job-seeking behavior of South Asian females living in the United States, Canada, United Kingdom, Germany, India, and Pakistan. We also applied a structural equation model to examine the role of enjoyment and job search self-efficacy in mediating the relationship between frequency of exposure to Bollywood movies and job-seeking behavior. Results indicated that exposure to Bollywood movies was positively related to enjoyment and job-seeking behavior of the female viewers of Bollywood movies. We also found a significant relationship between job search self-efficacy and job-seeking behavior. Our study offers a significant insight into the role of entertainment narratives in influencing the behavior of South Asian female audiences that hitherto remained a neglected group in media effects research.